Nutrisi Enteral Jangka Pendek Tinggi Serat, Khusus Diabetes pada Pasien Lanjut Usia dengan Diabetes Melitus Tipe 2 – Laporan Kasus: Laporan Kasus - Simatupang, Yustina Rossa; Wangsa, Andrean; Nareswara, Anastu Regita; Setiyaningrum, Melinda; Putra, Dendy Daffa Anugrah (PT Kalbe Farma Tbk., 2026)
Introduction: High-fiber diabetes-specific formulas (DSFs) are designed to support glycemic control in patients with type 2 diabetes mellitus (T2DM), particularly those requiring nutritional support. Despite their potential benefits, evidence regarding their short-term effects on blood glucose levels and insulin requirements remains limited. This case report explores the impact of an oral DSF on glycemic control in an elderly patient with T2DM over a four-day inpatient period. Case: A 70-year-old overweight woman (BMI 24.6 kg/m²) was hospitalized due touncontrolled hyperglycemia (HbA1c 10.6%, fasting glucose 469 mg/dL) with poor oral intake (< 50% of needs) secondary to nausea and vomiting. A standardized DSF was administered orally alongside a diabetic soft diet for 4 days. DSF was introduced at 150 mL three times daily and titrated to 200 mL twice daily, contributing to a total intake of approximately 1,500 kcal/day. Insulin doses (10 IU regular insulin three times a day) remained unchanged. Monitoring included daily fasting glucose and clinical tolerance. Fasting blood glucose decreased from 469 mg/dL on day 1 to 260 mg/dL by day 4. The patient showed improved oral intake (up to 75% of caloric needs) and better appetite without gastrointestinal complaints. No hypoglycemia episodes or insulin dose adjustments were necessary. Discussion: During the four-day observation period, fasting blood glucose decreased progressively from 469 mg/dL to 260 mg/dL without modification of insulin dosage. Oral intake improved to approximately 75% of estimated needs, and no hypoglycemic episodes or gastrointestinal intolerance were observed. The improvement in glycemic trends occurred alongside structured nutritional support and consistent insulin therapy. Conclusion: Short-term administration of a high-fiber DSF improved glycemic trends and nutritional intake in an elderly T2DM patient without adverse effects. DSF can be an effective adjunct in individualized medical nutrition therapy to support glycemic stabilization during hospitalization.